Podobieństwa i różnice w podejściu do nauki języka obcego pomiędzy osobami jednojęzycznymi i wielojęzycznymi - Górska, Agnieszka (Investigationes Linguisticae, 2011)
This paper presents results of three comparisons: first, between monolinguals and multilinguals, second, between simultaneous multilinguals and consecutive multilinguals, and third, between simultaneous multilinguals and monolinguals. The aim of the research was to determine whether those groups differ in their approach towards the language learning process. Some differences between multilinguals and monolinguals were found. The paper may be of interest to those who investigate motivation and language learning strategies.